Եկեղեցական իշխանության ճակատագիրը արաբների նվաճած Բյուզանդական Հայքի գավառներում - Արսեն Շահինյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье рассматривается судьба церковной власти на землях Великой Армении и Малой Армении, которые накануне великих завоеваний арабов-мусульман, пребывая в составе Византийской империи, подчинялись либо Константинопольскому или Антиохийскому патриархатам, либо Двинскому католикосату Армянской Церкви, а по итогам арабо-византийских войн второй половины VII в. достались халифату Умаййадов (661–750). The article discusses the fate of church authority in the lands of Greater Armenia and Lesser Armenia, which, on the eve of the great conquests of Muslim Arabs, being part of the Byzantine Empire, were under the jurisdiction of either the Patriarchate of Constantinople or Patriarchate of Antioch, or the Catholicosate of Dvin of the Armenian Church, and passed to the Umayyad Caliphate (661–750) following the ArabByzantine wars of the second half of the 7th century․
Keywords: History; Philology; Linguistics; Language and Literature